African American, Postrelease, Opioid, Female Offenders' Experiences in Job Interviews - Dunmore, Wanda (2019)
The increasing recidivism rate for African American female offenders is exacerbated by postrelease job candidates' difficulties with interviewing for employment. The purpose of this hermeneutical, phenomenological study was to examine experiences from postrelease, African American, female, opioid offenders when interviewing with potential employers. Critical race Black feminist theory was used as the ontological lens for this research. Criterion sampling was used to recruit 12 female African American opioid female research participants. Data collection occurred via 12 semistructured, face-to-face interviewees. Thematic analysis was used to develop common emergent themes from the lived experiences of postrelease, African American, female, opioid offenders. Results showed that postrelease, African American, female offenders experienced emotional responses such as stress, nervousness, and anxiety during the interview process. In addition, they feared rejection when informing potential employers about their criminal background. The findings are significant in developing training programs for transition, human service, and criminal justice agencies that can increase the chances of postoffender, African American, female, opioid drug offender employment and decrease recidivism